Understanding researchers' intention to publish in open access journals. Issue 6 (9th October 2017) - Moksness, Lars; Olsen, Svein Ottar
Abstract : Purpose: The purpose of this paper is to understand how attitudes, norms (injunctive and descriptive) and perceived behavioral control (PBC) (capacity and autonomy) influence the intention to publish open access (OA), and how personal innovativeness in information technology affects attitude and PBC. Design/methodology/approach: This study employs an integrated and extended theory of planned behavior (TPB) framework within a cross-sectional survey design. The sample consists of researchers at a Norwegian university, and data are collected digitally via e-mail invitation and analyzed using structural equation modeling. Findings: This study determines that attitude is the strongest predictor of the intention to publish OA, followed by injunctive and descriptive social norms, and PBC capacity and autonomy. All factors positively influence intention apart from PBC autonomy, which has a negative effect. Research limitations/implications: Potential limitations include: a relatively small sample size, self-reported data and employing intention, not behavior, as the ultimate dependent variable. Practical implications: This research contributes with a deeper understanding of what drives the intention to publish OA research articles, and how innovativeness affects attitudes and PBC autonomy. Support is found for an extended TPB model with decomposed normative and PBC components. This knowledge is essential in creating an impetus for systematic research on OA publishing behavior. Originality/value: Theory-driven research into understanding OA publishing behavior is rare. Decomposing the normative and PBC constructs is uncommon in TPB research, and a novel approach in OA research. Personal innovativeness has not been explored previously in relation to OA publishing.